Pengembangan Jati Diri Melalui Refleksi dan Eksplorasi : Peran Lingkungan Serta Cipta, Rasa, dan Karsa Dalam Membangun Kepercayaan Diri (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Education plays a very important role in the process of improving the quality of human resources. Improving the quality of education is a process that is integrated with the process of improving the quality of human resources themselves. Improving the quality of human resources, namely development in building self-identity, can be achieved through a process that involves in-depth reflection and exploration of individual potential. This research aims to analyze the role of the environment and the elements of creativity, feeling and initiative in building self-confidence as part of forming one's identity. The environment, whether family, education, or society, plays a major supporting role in providing space that facilitates self-exploration. Meanwhile, the elements of creativity, feeling, and initiative become the internal foundation that moves individuals to recognize potential, face challenges, and achieve their life goals. With this development of identity, it is hoped that this can be a solution for them to gain progress, namely self-confidence, by helping to contribute to various activities, apart from that it can also make them balanced individuals who have great concern for the environment.